Rapid and Sensitive Fluorescence Detection of Staphylococcus aureus Based on Polyethyleneimine-Enhanced Boronate Affinity Isolation - Yujia Xu; Hongwei Zheng; Jianxin Sui; Hong Lin; Limin Cao (Foods, 2023)
There are increasing demands for fast and simple detection of pathogens in foodstuffs. Fluorescence analysis has demonstrated significant advantages for easy operation and high sensitivity, although it is usually hindered by a complex matrix, low bacterial abundance, and long-term bacterial enrichment. Effective enrichment procedures are required to meet the requirements for food detection. Here, boronate-functionalized cellulose filter paper and specific fluorescent probes were combined. An integrated approach for the enrichment of detection of Staphylococcus aureus was proposed. The modification of polyethyleneimine demonstrated a significant effect in enhancing the bacterial enrichment, and the boronate affinity efficiency of the paper was increased by about 51~132%. With optimized conditions, the adsorption efficiency for S. aureus was evaluated as 1.87 × 108 CFU/cm2, the linear range of the fluorescent analysis was 104 CFU/mL~108 CFU/mL (R2 = 0.9835), and the lowest limit of detection (LOD) was calculated as 2.24 × 102 CFU/mL. Such efficiency was validated with milk and yogurt samples. These results indicated that the material had a high enrichment capacity, simple operation, and high substrate tolerance, which had the promising potential to be the established method for the fast detection of food pathogens.